Potential of Standard Perinatal Data for Measuring Violation of Birth Integrity - Miani, Céline; Batram-Zantvoort, Stephanie; Wandschneider, Lisa; Spallek, Jacob; Razum, Oliver (Frontiers in Global Women's Health, 2021)
Background Measuring the phenomenon of violation of birth integrity (vBI) (e.g. obstetric violence) relies in part on the availability and content of maternity care providers’ data. The population coverage and linkage possibilities that these data provide make for a yet untapped potential. Although vBI is a complex phenomenon best measured with dedicated instruments, we argue that maternity care providers’ data could contribute to enhance our knowledge of the manifestations and frequency of vBI, and allow for analyses across different sub-groups of the population. Looking into the German standardised perinatal data, we investigate which variables are relevant to vBI-related research, and how complete their reporting is. Methods First, we analyse state-of-the-art frameworks and recommendations, and, for each vBI-related domain, we search for and list corresponding variables in the perinatal data which could contribute to a better understanding of vBI issues. Second, we use an example and analyse the content of perinatal data obtained between 2013 and 2016 in the context of the BaBi birth cohort study set in Bielefeld, Germany. We use descriptive statistics to assess the completeness of the data. Results The vBI-related variables can be classified in three main categories: discrimination based on specific patient socio-demographic attributes (e.g. height and weight to calculate BMI before pregnancy, foreign origin), indication for medical interventions (i.e. medicalization-related variables: indication for caesarean sections and induction), and supportive care, in particular the mobilization dimension (e.g. continuous fetal heartbeat monitoring). The data analyses included 876 births, of which 601 were vaginal birth. We found poor reporting on demographic variables in terms of completeness. Medicalization and mobilization variables are better documented, although limited in scope. Conclusions Putting more emphasis on the completeness of standardised data could increase their potential for vBI-related research. Perinatal data alone are insufficient to assess vBI, but a broader, theory-informed discussion of indicators to be included in standardised datasets would contribute to capturing the different aspects of integrity violation in a more systematic way and expand the evidence-base on different types of vBI.